2010
DOI: 10.1007/s12529-010-9110-0
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and Psychological Reactivity and Recovery from Harassment in a Biracial Sample of High and Low Hostile Men and Women

Abstract: Although the predicted interaction between hostility and harassment was not supported in the context of cardiovascular responses, such an interaction was observed in the context of blame attributions, whereby harassed hostile participants were found to blame others for their task performance than the other subgroups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 79 publications
(136 reference statements)
0
4
0
Order By: Relevance
“…3a), even after accounting for sex differences in body mass index and baseline levels. A few studies, however, have failed to find sex differences in heart rate reactivity (Kelly et al, 2008; Neumann et al, 2010; Strahler et al, 2010), indicating that this effect may not be as robust as the SBP effects in adults. In fact, evidence suggests that the inconsistencies in heart rate studies may reflect the moderating influence of polymorphisms in the serotonin transporter gene-linked polymorphic region (5-HTTLPR).…”
Section: Sex Differences In Physiological Reactivitymentioning
confidence: 99%
“…3a), even after accounting for sex differences in body mass index and baseline levels. A few studies, however, have failed to find sex differences in heart rate reactivity (Kelly et al, 2008; Neumann et al, 2010; Strahler et al, 2010), indicating that this effect may not be as robust as the SBP effects in adults. In fact, evidence suggests that the inconsistencies in heart rate studies may reflect the moderating influence of polymorphisms in the serotonin transporter gene-linked polymorphic region (5-HTTLPR).…”
Section: Sex Differences In Physiological Reactivitymentioning
confidence: 99%
“…Within the framework of social determinants of health the aim of the Editorial for this issue of International Journal of Behavioral Medicine is to emphasize six studies of psychological and social conditions under different phases of life in relation to a number of health-related outcomes as illustrated in Fig. 2 [3][4][5][6][7][8].…”
mentioning
confidence: 99%
“…Brindle et al, ). A number of studies have found blunted cardiovascular responses to be associated with maladaptive mood and mental health statuses (e.g., Neumann et al, ; Phillips, Hunt, Der, & Carroll, ). In recent years, some work suggests that blunted patterns of stress responsivity may reflect similarly negative health consequences as those associated with exaggerated stress responding (e.g., Hughes, Lü, & Howards, ; Lovallo, ; Phillips, Ginty, & Hughes, ).…”
Section: Discussionmentioning
confidence: 99%